Application of learning discovery learning model combined media audiovisual on students achievement in material excretion system in madrasah aliyah Banda Aceh - Fazrina Fazrina; Khairil Khairil; Ismul Huda (Jurnal Edubio Tropika, 2018)
This study aims to determine the effect of application model discovery learning combined audiovisual media on student learning outcomes in the material excretory system. Data collected in February until March 2017. The method used in this study is a quasi-experimental design with the matching only pretest-posttest control group design with sample 110 students. The research conducted in the experimental class and control class. The instrument used was a test to assess student learning outcomes. Analysis of data using test Mann Whitney U at significant level 0.05. The results showed Sig. (2-tailed) 0.000 0.05. Conclusion, The learning model discovery, learning combined audiovisual media significantly influence student learning outcomes in the material excretory system.